2021
DOI: 10.1002/jsfa.11030
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan stimulates secondary metabolite production and nutrient uptake in medicinal plant Dracocephalum kotschyi

Abstract: BACKGROUND A wide variety of secondary metabolites are synthesized from primary metabolites by plants which have a vast range in pharmaceutical, food additive and industrial applications. In recent years, the use of elicitors has opened a novel approach for the production of secondary metabolite compounds. Dracocephalum kotschyi is a valuable herb due to pharmaceutical compounds like rosmarinic acid, quercetin and apigenin. In the current study, foliar application of chitosan (0, 100, 400 mg L−1) as an elicito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 61 publications
1
9
2
Order By: Relevance
“…polyphenol oxidase and β-1, 3-glucanases, were enhanced after chitosan elicitation in Ocimum basilicum L. and Melissa officinalis L. (Hawrylak-Nowak et al, 2021). (Kahromi and Khara, 2021) indicated that the amounts of hydrogen peroxide and the activities of enzymatic and non-enzymatic and nutrient absorption increased after the foliar spray of chitosan.…”
Section: 22(2): 264-288 Print: Issn 1687-1464mentioning
confidence: 96%
“…polyphenol oxidase and β-1, 3-glucanases, were enhanced after chitosan elicitation in Ocimum basilicum L. and Melissa officinalis L. (Hawrylak-Nowak et al, 2021). (Kahromi and Khara, 2021) indicated that the amounts of hydrogen peroxide and the activities of enzymatic and non-enzymatic and nutrient absorption increased after the foliar spray of chitosan.…”
Section: 22(2): 264-288 Print: Issn 1687-1464mentioning
confidence: 96%
“…Zn can also induce the expression of defense-related genes, such as those involved in synthesizing phytoalexins, which are antimicrobial compounds that may help plants ward off disease [ 106 ]. In addition, Zn can stimulate the production of secondary metabolites, such as flavonoids, with antimicrobial properties [ 107 , 108 ]. Zn also helps maintain the structural integrity of plant tissues, which can prevent pathogen invasion.…”
Section: Role Of Metals In Insectsmentioning
confidence: 99%
“…The dose-response curve also provides critical data for understanding variations attributed to time, plant species, or environmental parameters (Belz et al, 2005). Beyond herbicides, there are examples of compounds, such as elicitor, which at low doses are used to induce or enhance stress mechanisms in plants to stimulate secondary metabolite production, but at elevated concentration are fatal (Kahromi & Khara, 2021;Narayani & Srivastava, 2017). The "exposure-response" of plants to various exogenous xenobiotics may result in similar, stimulatory or inhibitory effects.…”
Section: Plant Pharmacodynamicsmentioning
confidence: 99%